A SPATIAL PERSPECTIVE OF BIOECONOMY IN THE BRAZILIAN AMAZON/Uma perspectiva espacial da bioeconomia na Amazônia brasileira - Arruda de Oliveira, Thiago José; Eichemberger Ummus, Marta; Pizarro Muñoz, Andrea Elena; Leocadio Vasco , Kennedy Douglas (Informe GEPEC, 2024)
This study investigates the distribution and diversity of activities related to bioeconomy in the Brazilian Amazon, leveraging concepts from spatial analysis such as rural-urban integration, agglomeration economies, and local-global knowledge. Methodologically, formal job data at the municipal level is analyzed, employing the Standardized Location Quotient (SLQ) alongside additional analyses. The findings reveal a network centered around Manaus-AM and other state capitals, where bio-industries (agroindustry and biotechnologies) are concentrated over time. These agglomerations are surrounded by regional economies specializing in groups of bioeconomy, such as farming, nature, or livestock production. However, the “spatial bioeconomy” in the Amazon highlights a limitation in the utilization of landscapes for multiple activities, signaling a challenge in enhancing biodiversity in the long term. Despite this, institutions within the Brazilian Amazon possess the capacity to implement projects of bioeconomy with positive impacts on local communities. In conclusion, this approach emerges as a crucial conduit for expanding spatial interactions while simultaneously addressing environmental and social concerns within regions abundant in bioresources. Resumo: Este estudo investiga a distribuição e diversidade das atividades relacionadas à bioeconomia na Amazônia brasileira, adotando conceitos de análise espacial, como integração rural-urbana, economias de aglomeração e conhecimento local-global. A metodologia utilizou de dados formais de emprego em nível municipal, aplicando-os no Quociente de Localização Padronizado (SLQ) e em análises adicionais. Os resultados revelam uma rede centrada em Manaus-AM e outras capitais estaduais, onde as bioindústrias (agroindústria e biotecnologias) concentraram-se ao longo do tempo. Essas aglomerações estão cercadas por economias regionais especializadas em agrupamentos da bioeconomia, como agricultura, natureza ou pecuária. No entanto, a “bioeconomia espacial” amazônica sugere uma limitação na diversificação de atividades em um mesmo local, sinalizando um desafio em melhorar os níveis de biodiversidade no longo prazo. Apesar disso, instituições dentro da Amazônia brasileira possuem a capacidade de executar projetos da bioeconomia com impactos positivos nas comunidades locais. Em conclusão, esse conceito emerge como um meio crucial para expandir as interações espaciais, ao mesmo tempo em que aborda questões ambientais e sociais em regiões abundantes de recursos biológicos.